Contemporary Organizational Paradigm - Maldun, Syamsuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Contemporary perspectives on organizational theory include organizational institutionalism, convention analysis, network analysis, knowledge studies, discourse studies, and practice studies. These perspectives offer new ways of understanding and analyzing contemporary organizational life, making them valuable resources for junior researchers and graduate students. Additionally, the evolution of organizational studies has led to the emergence of new approaches such as resource dependence, population ecology, structural contingency, new institutional economics, and new institutionalism. These approaches provide important theoretical references for the evolution and systematization of contemporary organizational studies, enhancing our understanding of how to analyze organizations. The increasing productivity and complexity of the organizational environment also influence the evolution of organizational theory, leading to the adoption of new complexity paradigms with nonlinear behavior as the current main paradigm. Overall, contemporary organizational theory encompasses a range of perspectives and approaches that contribute to a deeper understanding of organizations and their dynamics